CONTEMPORARY MARKETING MANAGEMENT STRATEGIES: NAVIGATING COMPLEXITY AND CHALLENGES IN THE DYNAMIC INDUSTRY ERA - Abdul Rosid; Loso Judijanto; Muhamad Stiadi; Rostini; Mohammad Taqiuddin Mohamad (CV. Adiba Aisha Amira, 2025)
This study delved into contemporary marketing management strategies, exploring their effectiveness in navigating complexity within the dynamic industry era. A comprehensive analysis of critical elements revealed their pivotal roles, including product innovation, dynamic pricing, diversified targeting, and technological adaptation. The study highlighted the importance of product innovation, emphasizing its role in meeting current consumer needs and anticipating future demands. Dynamic pricing strategies, encompassing variable pricing models and personalized approaches, enhanced adaptability in response to evolving market conditions. Diversified targeting, involving market segmentation and nuanced market positioning, emerged as crucial for engaging diverse consumer bases effectively. Additionally, the study underscored the significance of adapting to technological trends, emphasizing the role of data analytics and the impact of artificial intelligence on marketing automation. By comprehensively examining these strategies, the study contributes valuable insights for businesses aiming to navigate the complexities of the contemporary marketing landscape and thrive in the ever-changing industry environment.